An exploratory study of parent involvement in early childhood development centres in Masiphumelele, Cape Town - Dube, Primrose Sikhanyiso (Department of Social Development, 2016)
This study explored parent involvement in Early Childhood Development (ECD) centres in Masiphumelele, Cape Town. The researcher aimed to gain an understanding of the following; how parents are involved in Early Childhood Development centres, factors that enhance parent involvement in ECD centres, factors that hinder parent involvement in ECD centres and challenges faced by parents in getting involved in ECD centres. This research study adopted a qualitative, exploratory approach using a semi-structured interview schedule. The researcher used non-probability, purposive sampling to select the participants. Nineteen participants were interviewed using an interview schedule as a guide. The data collected was analyzed using Tesch's (1990) method of analysis. The research findings revealed that even though there are parents who participate in activities taking place at ECD centres, there is still lack of parent involvement in ECD centres. The thesis affirms that unity among parents, take-home activities, hosting general parent meetings, effective communication between parents and ECD staff especially teachers, parent days, hosting parent workshops, adopting a positive attitude towards parents, parent class visits and adequate physical space are factors that enhance parent involvement in ECD centres. Evidence from the research study show that lack of time, single parenthood, lack of interest, lack of education, poverty and unemployment are factors that inhibit parent involvement in ECD centres. According to the research findings, challenges that parents face in getting involved are; coping, trust issues, participation in education activities, provision of basic needs and payment of ECD centre fees. The study recommends that ECD centres should initiate parent involvement programmes so that parents gain skills and self-confidence. Parents are then more likely to be involved in their children's education.